Acculturation of Javanese and Malay Ethnic Marriage (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study was conducted to obtain information about the acculturation process of Javanese and Malay ethnic marriages. This research was conducted in Kisaran, Asahan Regency, North Sumatra Province. This study used a qualitative descriptive method that aimed to provide an overview of acculturation through Ethnic Intermarriage of the Malay and Javanese ethnic group in Kisaran. In collecting the data, the writer used the documentary technique through purposive sampling. The data were collected through interviews, observation and documentation. The subjects in this study were ten people, namely five married spouses who carried out Javanese and Malay ethnic marriage. This study indicated that the acculturation processed through Ethnic Intermarriage of Javanese and Malay ethnic occurred in a series of marriage traditions. The acculturation of marriages that occurred in Javanese and Malay ethnicities in Kisaran was in the integration strategy. Which still maintain each culture in the traditional wedding.
Keywords: Aculturation; Interethnic Marriage; Javanese; Malay